Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the equation [tex]\(3(x + 1) = 2(x - 1)\)[/tex], let's go through the steps to isolate and solve for [tex]\(x\)[/tex].
1. Begin by distributing the constants on both sides of the equation:
[tex]\[ 3(x + 1) = 3 \cdot x + 3 \cdot 1 = 3x + 3 \][/tex]
[tex]\[ 2(x - 1) = 2 \cdot x - 2 \cdot 1 = 2x - 2 \][/tex]
2. Now, the equation looks like this:
[tex]\[ 3x + 3 = 2x - 2 \][/tex]
3. To isolate [tex]\(x\)[/tex], we need to get all terms involving [tex]\(x\)[/tex] on one side of the equation and the constant terms on the other side. First, subtract [tex]\(2x\)[/tex] from both sides:
[tex]\[ 3x - 2x + 3 = -2 \][/tex]
[tex]\[ x + 3 = -2 \][/tex]
4. Next, subtract 3 from both sides to solve for [tex]\(x\)[/tex]:
[tex]\[ x + 3 - 3 = -2 - 3 \][/tex]
[tex]\[ x = -5 \][/tex]
So, the solution for [tex]\(x\)[/tex] is [tex]\(-5\)[/tex].
Among the given choices:
[tex]\[ -5, -4, -2, -1 \][/tex]
The correct answer is [tex]\(-5\)[/tex].
1. Begin by distributing the constants on both sides of the equation:
[tex]\[ 3(x + 1) = 3 \cdot x + 3 \cdot 1 = 3x + 3 \][/tex]
[tex]\[ 2(x - 1) = 2 \cdot x - 2 \cdot 1 = 2x - 2 \][/tex]
2. Now, the equation looks like this:
[tex]\[ 3x + 3 = 2x - 2 \][/tex]
3. To isolate [tex]\(x\)[/tex], we need to get all terms involving [tex]\(x\)[/tex] on one side of the equation and the constant terms on the other side. First, subtract [tex]\(2x\)[/tex] from both sides:
[tex]\[ 3x - 2x + 3 = -2 \][/tex]
[tex]\[ x + 3 = -2 \][/tex]
4. Next, subtract 3 from both sides to solve for [tex]\(x\)[/tex]:
[tex]\[ x + 3 - 3 = -2 - 3 \][/tex]
[tex]\[ x = -5 \][/tex]
So, the solution for [tex]\(x\)[/tex] is [tex]\(-5\)[/tex].
Among the given choices:
[tex]\[ -5, -4, -2, -1 \][/tex]
The correct answer is [tex]\(-5\)[/tex].
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.